The Development Model of Women-friendly and Child-caring Village from the Perspective of Women in Development - Hidayaturahmi, ‎; Rosidanti, Hamidah; Anita, ‎ (KnE Social Sciences, 2025)
This study aims to determine women’s roles in village development and to design a model of women-friendly, sustainable, child-care villages (Desa Ramah Perempuan dan Peduli Anak) to promote sustainable development. It employs an exploratory qualitative research approach, which involves explaining and evaluating phenomena using person and group-based data and information in under-developed communities in Gunung Rante Village and Bandar Rahmat Village, North Sumatra Province. According to the study, women’s responsibilities in undeveloped regions are limited to reproductive tasks and do not yet reflect that of the women in development strategy which places women in roles both inside and outside the household. This is while women’s societal roles remain lowly and far behind men’s. A sustainable village model is the ideal design for a women-friendly and child-care village model for undeveloped village populations and aligns with the Sustainable Development Goals from a village perspective (village SDGs), that strengthen the following areas: balanced parenting routine between father and mother, empowering women in entrepreneurship, nineyear basic education opportunities for women, free health services for women and children, and eradicating child labor. Understanding women in development must be implemented in empowering women productively and socially. The women-friendly and child-caring village model in underdeveloped villages must focus on strengthening the education and health sectors which are still problems in underdeveloped villages.